Teaching Behavioral Aspects of Performance Evaluation: An Experiential Approach. - Umapathy, Srinivasan (The Accounting Review, 1985)
ABSTRACT: Based on a careful examination of the traditional approach to teaching behavioral aspects of performance evaluation, this paper concludes that there are some serious instructional gaps in teaching the topic. The paper argues that new pedagogical approaches based on student-generated experiences are effective in teaching behavioral aspects of accounting. Two experiential exercises developed by the author are also presented and discussed in the paper. Finally, the paper recommends development and wider adoption of experiential exercises in teaching behavioral aspects of accounting.